Safety Enhancement in Fashion Design and Clothing Construction Laboratory in Tertiary Institutions in Anambra State - E. N., Emeka-Okafor (Journal of Home Economics Research, 2024)
The study focused on safety enhancement in fashion design and clothing construction laboratories in tertiary institutions in Anambra state. It was a survey. Three research questions guided the study. The population for the study was 27 lectures of Home Economics, Fashion design and clothing technology in three tertiary institutions in Anambra State and 423 students from these departments. Questionnaire was used for data collection. Data were analyzed using mean. Major findings include that carelessness and lack of repairs were major risk factors in the laboratory, while putting on protective garments, laying down strict safety rules will enhance safety.